Electricity Consumption and Green Mortgage: New Insights into the Threshold Cointegration Relationship - Lee, Nicholas; Su, Hsiang-Jane; Lin, Ming-Chin (International Journal of Energy Economics and Policy, 2018)
This paper examines threshold dynamics of electricity consumption and green mortgage. Industrial and individual electricity consumptions are considered respectively. We apply a threshold vector error correction model (TVECM) with a threshold endogenously model. An unusual regime is above a threshold, whereas below a threshold for a usual regime. Our results show threshold effects for total (or industrial) electricity consumption and green mortgage, suggesting structure changes with different asymmetric error-correction effects in the usual and unusual regimes. Specifically, in the unusual regime, the stronger effect in the total electricity consumption case for green mortgage causing electricity consumption than the opposite direction is found but the smaller effect in the industrial electricity consumption case. It implies that efficiency improvement will be proposed for a new plant and upgrades of existing plant. Therefore, our results should highlight the critical importance of using TVECM in empirical studies on threshold dynamics of electricity consumption and green mortgage. Keywords: Electricity consumption, green mortgage, threshold cointegration, nonlinear dynamics. JEL Classifications: C32, Q40, G12.